Urban ponds as nature-based solutions for heat mitigation and temperature regulation in highly urbanised regions - Xueqin Li; Lindsay C. Stringer; Hisako Nomura; Masaya Nakatsuka; Kouhei Shibazaki; Martin Dallimer (Landscape and Urban Planning, 2026)

Climate-induced forest destabilization and shrub stabilization in Africa - Linhai Cheng; Qiang Tang; Nan Lu; Yafeng Wang; Changjia Li; Shuai Wang; Xiangyi Li; Phuping Sucharitakul; Yongzhe Chen; Zhihong Xu; Lindsay C. Stringer; Bojie Fu (Global and Planetary Change, 2026)

New U-series dates on the Petralona cranium, a key-fossil for European human evolution: An answer to the reply ‘Can controversial samples lead to reliable conclusions?’ - C. Falguères; Q. Shao; C. Perrenoud; C. Stringer; O. Tombret; L. Garbé; A. Darlas (Journal of Human Evolution, 2026)

Positive Atlantic Multidecadal Oscillation–La Niña synergy enhances recent East Asian dust activity via hydrothermal anomalies - Ruibo Zhao; Xiaoming Feng; Changjia Li; Yun Yang; Lindsay C. Stringer; Bojie Fu (Science Bulletin, 2026)

Evidence-based steps towards climate resilient development pathways: Insights across levels and sectors - Nicola Favretto; Lindsay C. Stringer (Global Environmental Change, 2026)

A methodological approach for assessing cross-border supply chain exposure to climate change impacts on crop production and transport - Emilie Stokeld; Chris West; Simon Croft; Lindsay C. Stringer; Cornelia Auer (Climatic Change, 2026)

Community perceptions on conservation management and sustainability around the protected area reserves in Nasarawa State, North Central Nigeria - Banki T. Chunwate; Robert A. Marchant; Eleanor K.K. Jew; Lindsay C. Stringer (Environmental Development, 2026)

Effects of land-use change on soil total carbon pool: a meta-analysis - Zhuobing Ren; Changjia Li; Shuai Wang; Wenxin Zhou; Lindsay C. Stringer; Bojie Fu (Agriculture, Ecosystems & Environment, 2026)

Assessing the Feasibility of Productive Weed Use: A Decision Support Framework for Land Stakeholders - James P. Westfield; Elizabeth M. Wandrag; Lindsay C. Stringer (Anthropocene Science, 2025)

Identification of conservation priority areas on the Qinghai-Tibet Plateau considering habitat, biodiversity, ecosystem services, and human well-being - Yazhe Li; Changjia Li; Wenxin Zhou; Shuai Wang; Yue Cao; Zhao Li; Tong Lu; Lindsay C. Stringer (Journal of Environmental Management, 2025)

Break the Political Deadlock on Drought Through an Integrated Policy Approach - Lindsay C. Stringer; Johannes Kruse; Mariam Akhtar-Schuster; Rodrigo Andrade Ramirez (Anthropocene Science, 2025)

A Middle and Late Devensian sequence from the northern part of Kents Cavern (Devon, UK) - Rob Dinnis; John Boulton; Barry Chandler; Jesse Davies; Jennifer C. French; Thomas Higham; Louisa Jáuregui; Mark Lewis; Matthias Meyer; Danielle Schreve; Chris Stringer; Chris Proctor (Journal of Quaternary Science, 2025)
1920s/30s excavation of a Middle Devensian sequence in the northern part of Kents Cavern recovered important Late Middle and Early Upper Palaeolithic archaeological material, including Britain's oldest known Homo sapiens remains. Questions remain about this material, including how it came to be in the cave. Judged by the recorded distribution of finds it may have entered via the Northeast Gallery. A previously unrecorded entrance into the cave from the Northeast Gallery was identified in 2014, and a column through the entrance's sedimentary fill was excavated during 2015–2016. The results of that work are reported here. The entrance retains an intact and well‐stratified Pleistocene sequence comparable to the ‘Cave Earth’ unit described previously inside the cave. The uppermost part of the newly recognised Northeast Gallery entrance sequence has been removed by historical excavation, with most of the remaining sediments spanning the Middle Devensian and earlier part of the Late Devensian. The sequence contains bone and pollen, and ancient mammalian DNA is preserved within the sediments. The base of the Northeast Gallery entrance sequence is formed of a clayey diamict comparable to the cave's ‘Breccia’ unit, a deposit currently understood as Middle Pleistocene, and previously identified only in Kents Cavern's southern chambers. Comparison of the excavated sequence with the historical record of the Vestibule excavation shows that the basal cave earth deposits in the Northeast Gallery entrance are significantly higher than those inside the cave. Although requiring further work to confirm, this suggests that the Northeast Gallery could have played a major role in the accumulation of material in the Vestibule during the Middle Devensian.

Detecting Zone‐Type Thresholds for Soil Organic, Inorganic, and Total Carbon Pools in China's Drylands - Zhuobing Ren; Changjia Li; Bojie Fu; Wenxin Zhou; Xinli Chen; Shuai Wang; Lindsay C. Stringer (Global Change Biology, 2025)
Growing concerns about the accelerating global changes in drylands have intensified interest in understanding the impacts of diverse environmental factors on various soil carbon components, particularly their potential threshold effects, which may lead to abrupt nonlinear changes in both the quantity and composition of soil carbon. However, most research has predominantly focused on identifying key environmental drivers of either organic or inorganic carbon separately, often neglecting the presence and range of multiple critical thresholds. This study addresses this gap by analyzing extensive field data, including soil carbon measurements and ecosystem variables, collected across a ~4000 km transect in China's drylands. Utilizing a gradient forest model combined with threshold analyses, we assess the impacts of key drivers, including sand content, total nitrogen, aridity, and cation exchange capacity, on soil carbon pools. Our findings indicate that nitrogen content is the most influential factor for soil organic carbon, which was sensitive to low levels of nitrogen (0.07%–0.08%), with a slower response observed at higher levels. Aridity significantly affects both organic and inorganic carbon pools, with identified threshold zones for organic carbon at aridity levels of 0.48–0.52 and 0.75–0.85, and for inorganic carbon at 0.82–0.88. Threshold zones of sand content for total carbon are identified at lower levels and a wider range (51.4%–64.1% and 87.3%–88.1%), due to its negative effects on both organic and inorganic carbon, impacting 20% of the dryland area. Spatial variations in threshold effects revealed a trade‐off between nitrogen and pH in regulating soil total carbon. The combined threshold effects of climate warming and aridification may pose a greater threat to soil organic carbon in high‐latitude regions. This research enhances understanding of soil carbon dynamics in arid environments and offers novel approaches and insights for identifying thresholds in ecosystems that are increasingly at risk of reaching tipping points.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Climate resilient development in vulnerable geographies - Nicola Favretto; Lindsay C. Stringer (Mitigation and Adaptation Strategies for Global Change, 2024)
The Intergovernmental Panel on Climate Change highlights the urgent need to operationalise Climate Resilient Development Pathways (CRDP), adopting mitigation and adaptation measures to secure a safe climate, meet human needs under a changing climate and enable sustainable development. Analyses have not yet compared different vulnerable geographies to understand similarities and differences in the constraints and opportunities in operationalising CRDP. Using conventional narrative literature review, this paper assesses CRDP across some of the world’s most vulnerable geographies: highlands (mountains), drylands and islands. It asks: (1) how are climate impacts experienced across highlands, drylands and islands and (2) what types of adaptation and mitigation are being employed across these vulnerable geographies? Key steps are discussed in moving towards CRDP via multiple enabling conditions. Findings show shared impacts across geographies include impacts on ecosystems, fisheries, agriculture and water systems, livelihood failure, food insecurity, and degradation of human health, inequality, losses to economic sectors, human migration and conflict, and cascading transboundary impacts. Adaptation and mitigation actions tend to focus on promoting nature-based approaches, livelihood diversification and economic development, harnessing mixed knowledges and policy and institutional measures. Actions with potential to accelerate transitions towards CRDP should focus on the specific arenas of engagement shaping the underlying vulnerability context of each geography, including the socio-cultural context, politics, governance and institutions, the economic and financial systems, knowledge availability, and technological capabilities.

Subnational perspectives on energy transition pathways for Mexico's electricity grid - Esteban Ricardo García Clavel; Thomas Stringer; Julio C. Sacramento Rivero; Manuel Burelo (Utilities Policy, 2024)

Artisanal and small-scale gold mining governance and cross-sectoral policy coherence in Ghana - Enoch Adranyi; Lindsay C. Stringer; Henrice Altink (Resources Policy, 2024)

The forgotten bread oven: local bakeries, forests and energy transition in Nigeria - Abubakar Tanimu Salisu; Aliyu Salisu Barau; Jamie A. Carr; Banki T. Chunwate; Eleanor K.K. Jew; Joshua D. Kirshner; Robert A. Marchant; Julia Tomei; Lindsay C. Stringer (Regional Environmental Change, 2024)

Integration of subcritical water extraction and treatment with xylanases and feruloyl esterases maximises release of feruloylated arabinoxylans from wheat bran - Reskandi C. Rudjito; Alvaro C. Matute; Amparo Jiménez-Quero; Lisbeth Olsson; Mary Ann Stringer; Kristian Bertel Rømer Mørkeberg Krogh; Jens Eklöf; Francisco Vilaplana (Bioresource Technology, 2024)

Land-based transportation influences carbon emission in urbanized China: A regional spatial spillover perspective - Chen Zeng; Bingqian Chai; Lindsay C. Stringer; Yangbiao Li; Zhen Wang; Xiangzheng Deng; Binbin Ma; Jinming Ren (Sustainable Cities and Society, 2024)

Effects of aridification on soil total carbon pools in China's drylands - Zhuobing Ren; Changjia Li; Bojie Fu; Shuai Wang; Lindsay C. Stringer (Global Change Biology, 2024)
Drylands are important carbon pools and are highly vulnerable to climate change, particularly in the context of increasing aridity. However, there has been limited research on the effects of aridification on soil total carbon including soil organic carbon and soil inorganic carbon, which hinders comprehensive understanding and projection of soil carbon dynamics in drylands. To determine the response of soil total carbon to aridification, and to understand how aridification drives soil total carbon variation along the aridity gradient through different ecosystem attributes, we measured soil organic carbon, inorganic carbon and total carbon across a ~4000 km aridity gradient in the drylands of northern China. Distribution patterns of organic carbon, inorganic carbon, and total carbon at different sites along the aridity gradient were analyzed. Results showed that soil organic carbon and inorganic carbon had a complementary relationship, that is, an increase in soil inorganic carbon positively compensated for the decrease in organic carbon in semiarid to hyperarid regions. Soil total carbon exhibited a nonlinear change with increasing aridity, and the effect of aridity on total carbon shifted from negative to positive at an aridity level of 0.71. In less arid regions, aridification leads to a decrease in total carbon, mainly through a decrease in organic carbon, whereas in more arid regions, aridification promotes an increase in inorganic carbon and thus an increase in total carbon. Our study highlights the importance of soil inorganic carbon to total carbon and the different effects of aridity on soil carbon pools in drylands. Soil total carbon needs to be considered when developing measures to conserve the terrestrial carbon sink.

Stakeholder perspectives on cross-border climate risks in the Brazil-Europe soy supply chain - Emilie Stokeld; Simon Croft; Tiago N.P. dos Reis; Lindsay C. Stringer; Chris West (Journal of Cleaner Production, 2023)

Arabinoxylan source and xylanase specificity influence the production of oligosaccharides with prebiotic potential - Reskandi C. Rudjito; Amparo Jiménez-Quero; Maria Del Carmen Casado Muñoz; Teun Kuil; Lisbeth Olsson; Mary Ann Stringer; Kristian Bertel Rømer Mørkeberg Krogh; Jens Eklöf; Francisco Vilaplana (Carbohydrate Polymers, 2023)

Effects of vegetation restoration on soil properties and vegetation attributes in the arid and semi-arid regions of China - Wenxin Zhou; Changjia Li; Shuai Wang; Zhuobing Ren; Lindsay C. Stringer (Journal of Environmental Management, 2023)

The impacts of artisanal and small-scale gold mining on rural livelihood trajectories: Insights from Ghana - Enoch Adranyi; Lindsay C. Stringer; Henrice Altink (The Extractive Industries and Society, 2023)

Effects of grazing and enclosure management on soil physical and chemical properties vary with aridity in China's drylands - Wenxin Zhou; Changjia Li; Shuai Wang; Zhuobing Ren; Lindsay C. Stringer (Science of The Total Environment, 2023)

Towards a holistic understanding of non-native tree impacts on ecosystem services: A review of Acacia, Eucalyptus and Pinus in Africa - Jasmine J. Wells; Lindsay C. Stringer; Anna J. Woodhead; Elizabeth M. Wandrag (Ecosystem Services, 2023)

Will global cobalt supply meet demand? The geological, mineral processing, production and geographic risk profile of cobalt - E. Savinova; C. Evans; É. Lèbre; M. Stringer; M. Azadi; R.K. Valenta (Resources, Conservation and Recycling, 2023)

Gas Flaring in Nigeria: A Multi-level Governance and Policy Coherence Analysis - Godwin O. Aigbe; Lindsay C. Stringer; Matthew Cotton (Anthropocene Science, 2023)
The unnecessary flaring of natural gas impacts public and environmental health, contributes to climate change and wastes fuel resources. Though reducing flaring is an emergent global environmental governance priority, progress has been slow. We assess gas flaring policy in the critical case of Nigeria through multi-level governance (MLG) structure. Our analysis assesses policy coherence (leading to progress in reaching shared goals) and divergence (creating tension and undermining progress) amongst sectors and institutional structures across the supranational, federal, state and local government scales. A combined dataset of documents, stakeholder interviews and expert surveys is analysed using Qualitative Document Analysis (QDA) and content analysis. We identify the principal actors involved, examine the extent of gas flaring awareness and policy coherence across multiple sectors/policy domains, and assess progress towards Nigeria’s national intended contribution and national policy on climate change mitigation. We find that policy coherence around gas flaring, including efforts towards climate change mitigation, has been slowed by political partisanship, poor governance, lack of regulatory compliance, and policy conflict between environmental protection and economic development priorities. Nigeria urgently requires inclusive involvement of stakeholder voices across multiple sectors and scales of local/regional government, the strengthening of federal institutions, a revaluation of economic aspirations through revenue diversification, and leadership that can temper the power of International Oil Companies (IOCs) to exploit the complexity of the MLG structure. These actions would help the government in improving environmental justice outcomes for flaring-affected communities.

Climate Resilient Development Pathways in Global Drylands - Lindsay C. Stringer; Nicholas P. Simpson; E. Lisa F. Schipper; Siri H. Eriksen (Anthropocene Science, 2022)
The Intergovernmental Panel on Climate Change (IPCC) Working Group II Report on Adaptation, Impacts and Vulnerability identifies the urgent need to embark upon Climate Resilient Development Pathways. Climate Resilient Development acknowledges that adaptation needs to be undertaken together with mitigation and development, in joined-up, inclusive, just and equitable ways, across multiple arenas of engagement. In highly vulnerable systems with complex development contexts, such as drylands, where globally, warming is already exceeding that of humid areas, urgent action is vital, as the window of opportunity for Climate Resilient Development is rapidly closing. This paper considers challenges and opportunities in charting Climate Resilient Development Pathways in the world’s drylands. It highlights the importance of stakeholder engagement and partnership building to harness diverse knowledge sources, situating equity and justice concerns at the core of decision making and actions such as land restoration. It notes that while technological solutions offer potential to advance Climate Resilient Development, they need to be developed in an inclusive manner and used in ways that do not undermine Indigenous knowledge and local knowledge or exacerbate inequalities. Many of the challenges to Climate Resilient Development go beyond technology to include highly contextual differences in understanding, environment, institutions and access to finance. Adequate assessment of trade-offs in Climate Resilient Development actions in drylands remains vital to the framing of Climate Resilient Development Pathways for different groups. The paper concludes by identifying major urgent research gaps considering upscaling, stakeholder responsibilities and governance, the magnitude of investment that is necessary, and the need for appropriate monitoring, evaluation and learning.

Advancing Global Biodiversity Governance: Recommendations for Strengthening the Post-2020 Global Biodiversity Framework - Priya Priyadarshini; Amit Kumar Bundela; Alexandros Gasparatos; Lindsay C. Stringer; Shalini Dhyani; Rajarshi Dasgupta; Chintala Sudhakar Reddy; Himlal Baral; Roldan Muradian; Madhav Karki; Purushothaman Chirakkuzhyil Abhilash; Josep Peñuelas (Anthropocene Science, 2022)

Climate change research and action must look beyond 2100 - Christopher Lyon; Erin E. Saupe; Christopher J. Smith; Daniel J. Hill; Andrew P. Beckerman; Lindsay C. Stringer; Robert Marchant; James McKay; Ariane Burke; Paul O’Higgins; Alexander M. Dunhill; Bethany J. Allen; et al. (Global Change Biology, 2022)
Anthropogenic activity is changing Earth's climate and ecosystems in ways that are potentially dangerous and disruptive to humans. Greenhouse gas concentrations in the atmosphere continue to rise, ensuring that these changes will be felt for centuries beyond 2100, the current benchmark for projection. Estimating the effects of past, current, and potential future emissions to only 2100 is therefore short‐sighted. Critical problems for food production and climate‐forced human migration are projected to arise well before 2100, raising questions regarding the habitability of some regions of the Earth after the turn of the century. To highlight the need for more distant horizon scanning, we model climate change to 2500 under a suite of emission scenarios and quantify associated projections of crop viability and heat stress. Together, our projections show global climate impacts increase significantly after 2100 without rapid mitigation. As a result, we argue that projections of climate and its effects on human well‐being and associated governance and policy must be framed beyond 2100.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Smallholder perceptions of land restoration activities: rewetting tropical peatland oil palm areas in Sumatra, Indonesia - Caroline Ward; Lindsay C. Stringer; Eleanor Warren-Thomas; Fahmuddin Agus; Merry Crowson; Keith Hamer; Bambang Hariyadi; Winda D. Kartika; Jennifer Lucey; Colin McClean; Neneng L. Nurida; Nathalie Petorelli; et al. (Regional Environmental Change, 2021)
The Indonesian government committed to restoring over 2 million ha of degraded peatland by the end of 2020, mainly to reduce peat fires and greenhouse gas emissions. Although it is unlikely the government will meet this target, restoration projects are still underway. One restoration strategy involves blocking peatland drainage canals, but the consequences of this for smallholder farmers whose livelihoods are dependent on agriculture are unclear. This paper investigates perceived impacts of canal blocks on smallholder farmers and identifies factors that affect their willingness to accept canal blocks on their land. We use data from 181 household questionnaires collected in 2018 across three villages in Jambi province, Sumatra. We found that the majority of respondents would accept canal blocks on their farms, perceiving that the blocks would have no impact on yields or farm access, and would decrease fire risk. Respondents who would not accept blocks on their farms were more likely to use canals to access their farms and perceive that canal blocks would decrease yields. The majority of farmers unwilling to accept canal blocks did not change their mind when provided with an option of a block that would allow boat travel. Our results improve understanding of why some smallholders may be unwilling to engage with peatland restoration. Further research is needed to understand the impact of canal blocks on smallholders’ yields. Engaging with stakeholders from the outset to understand farmers’ concerns, and perceptions is key if the government is to succeed in meeting its peatland restoration target and to ensure that the costs and benefits of restoration are evenly shared between local stakeholders and other actors.

Perceived Climate Variability and Compounding Stressors: Implications for Risks to Livelihoods of Smallholder Indian Farmers - Ranjay K. Singh; Anshuman Singh; Satyendra Kumar; Parvender Sheoran; D. K. Sharma; Lindsay C. Stringer; Claire H. Quinn; Arvind Kumar; Dheeraj Singh (Environmental Management, 2020)

Investigating the use of Paleolithic perforated batons: new evidence from Gough’s Cave (Somerset, UK) - C. Lucas; J. Galway-Witham; C. B. Stringer; S. M. Bello (Archaeological and Anthropological Sciences, 2019)

Climate change adaptation and cross-sectoral policy coherence in southern Africa - Matthew I. England; Andrew J. Dougill; Lindsay C. Stringer; Katharine E. Vincent; Joanna Pardoe; Felix K. Kalaba; David D. Mkwambisi; Emilinah Namaganda; Stavros Afionis (Regional Environmental Change, 2018)

Unravelling Stakeholder Perceptions to Enable Adaptive Water Governance in Dryland Systems - Gabriel Lopez Porras; Lindsay C. Stringer; Claire H. Quinn (Water Resources Management, 2018)

Climate compatible development reconsidered: calling for a critical perspective - Lisa Ficklin; Lindsay C. Stringer; Andrew J. Dougill; Susannah M. Sallu (Climate and Development, 2018)

Adaptation to Climatic Hazards in the Savannah Ecosystem: Improving Adaptation Policy and Action - Gerald A. B. Yiran; Lindsay C. Stringer (Environmental Management, 2017)

Investigating Climate Compatible Development Outcomes and their Implications for Distributive Justice: Evidence from Malawi - Benjamin T. Wood; Claire H. Quinn; Lindsay C. Stringer; Andrew J. Dougill (Environmental Management, 2017)

Mapping vulnerability to multiple hazards in the savannah Ecosystem in Ghana - Gerald A. B. Yiran; Lindsay C. Stringer; Emmanuel M. Attua; Andrew J. Evans; Andy J. Challinor; Edwin A. Gyasi (Regional Environmental Change, 2017)

Using a novel climate–water conflict vulnerability index to capture double exposures in Lake Chad - Uche T. Okpara; Lindsay C. Stringer; Andrew J. Dougill (Regional Environmental Change, 2017)

Evaluating the Potential for Harmonized Prediction and Comparison of Disposal‐Stage Greenhouse Gas Emissions for Biomaterial Products - David Glew; Lindsay C. Stringer; Adolf Acquaye; Simon McQueen‐Mason (Journal of Industrial Ecology, 2017)
Summary The carbon footprint (CF) of biofuels and biomaterials is a barrier to their acceptance, yet the greenhouse gas emissions associated with disposing of biomaterials are frequently omitted from analyses. This article investigates whether harmonization is appropriate for calculating the importance of biomaterials’ disposal. This research shows that disposal stages could double a biomaterial's CF, or reduce it to the point that it could claim to be zero carbon. Incineration with combined heat and power coupled with on‐site energy production in the biorefinery are identified as prerequisites to being zero carbon. The article assesses the current UK waste infrastructure's ability to support a low‐carbon bio‐based future economy, and finds that presently it only achieves marginal net reductions when compared to landfill and so cannot be said to support low‐carbon biomaterials, though the article challenges the polluter pays principle where low‐carbon disposal infrastructure are not available. Reuse and recycling are shown to have the potential to offset all the emissions caused by landfill of biomaterials. However, the savings are not so great as to offset the biomaterial's upstream emissions. The study explores the ability to overcome the barriers to incorporating disposal into life cycle assessment while identifying limitations of using harmonization as an assessment method. Specifically, data availability and industry consensus are flagged as major barriers. The study also uses sensitivity analysis to investigate the influence of methodological choices, such as allowing additional reuse and recycling stages, classifying biomaterials into different types, and choosing between opposing allocation methods.

Lake drying and livelihood dynamics in Lake Chad: Unravelling the mechanisms, contexts and responses - Uche T. Okpara; Lindsay C. Stringer; Andrew J. Dougill (Ambio, 2016)

Challenges to polycentric governance of an international development project tackling land degradation in Swaziland - Steven E. Orchard; Lindsay C. Stringer (Ambio, 2016)

The biodiversity of the United Kingdom’s Overseas Territories: a stock take of species occurrence and assessment of key knowledge gaps - Thomas Churchyard; M. A. Eaton; S. Havery; J. Hall; J. Millett; A. Farr; R. J. Cuthbert; C. Stringer; J. A. Vickery (Biodiversity and Conservation, 2016)

Soil properties of mangroves in contrasting geomorphic settings within the Zambezi River Delta, Mozambique - Christina E. Stringer; Carl C. Trettin; Stanley J. Zarnoch (Wetlands Ecology and Management, 2016)

Composition, biomass and structure of mangroves within the Zambezi River Delta - Carl C. Trettin; Christina E. Stringer; Stanley J. Zarnoch (Wetlands Ecology and Management, 2016)

Sustainability spaces for complex agri-food systems - Stephen Whitfield; Tim G. Benton; Martin Dallimer; Les G. Firbank; Guy M. Poppy; Susannah M. Sallu; Lindsay C. Stringer (Food Security, 2015)

Barriers to climate change adaptation: evidence from northeast Ghana in the context of a systematic literature review - Philip Antwi-Agyei; Andrew J. Dougill; Lindsay C. Stringer (Climate and Development, 2015)

Presenting Triple-Wins? Assessing Projects That Deliver Adaptation, Mitigation and Development Co-benefits in Rural Sub-Saharan Africa - Natalie Suckall; Lindsay C. Stringer; Emma L. Tompkins (Ambio, 2015)

An Exploration of Scenarios to Support Sustainable Land Management Using Integrated Environmental Socio-economic Models - L. Fleskens; D. Nainggolan; L. C. Stringer (Environmental Management, 2014)

Participatory Evaluation of Monitoring and Modeling of Sustainable Land Management Technologies in Areas Prone to Land Degradation - L. C. Stringer; L. Fleskens; M. S. Reed; J. de Vente; M. Zengin (Environmental Management, 2014)

Light brown apple moth (Epiphyas postvittana) (Lepidoptera: Tortricidae) colonization of California - D. M. Suckling; L. D. Stringer; D. B. Baird; R. C. Butler; T. E. S. Sullivan; D. R. Lance; G. S. Simmons (Biological Invasions, 2014)

Livelihood adaptations to climate variability: insights from farming households in Ghana - Philip Antwi-Agyei; Lindsay C. Stringer; Andrew J. Dougill (Regional Environmental Change, 2014)

Advancing climate compatible development: lessons from southern Africa - Lindsay C. Stringer; Andrew J. Dougill; Jen C. Dyer; Katharine Vincent; Florian Fritzsche; Julia Leventon; Mario Paulo Falcão; Pascal Manyakaidze; Stephen Syampungani; Philip Powell; Gabriel Kalaba (Regional Environmental Change, 2014)

The environment as a strategic priority in the European Union–Brazil partnership: is the EU behaving as a normative power or soft imperialist? - Stavros Afionis; Lindsay C. Stringer (International Environmental Agreements: Politics, Law and Economics, 2014)

Determinants of successful arthropod eradication programs - Patrick C. Tobin; John M. Kean; David Maxwell Suckling; Deborah G. McCullough; Daniel A. Herms; Lloyd D. Stringer (Biological Invasions, 2014)

Characterising the nature of household vulnerability to climate variability: empirical evidence from two regions of Ghana - Philip Antwi-Agyei; Andrew J. Dougill; Evan D. G. Fraser; Lindsay C. Stringer (Environment, Development and Sustainability, 2013)

Is rainfall really changing? Farmers’ perceptions, meteorological data, and policy implications - Elisabeth Simelton; Claire H. Quinn; Nnyaladzi Batisani; Andrew J. Dougill; Jen C. Dyer; Evan D.G. Fraser; David Mkwambisi; Susannah Sallu; Lindsay C. Stringer (Climate and Development, 2013)

Towards implementation and achievement of sustainable biofuel development in Africa - Ian Duvenage; Ros Taplin; Lindsay C. Stringer (Environment, Development and Sustainability, 2012)

Family Selection Improves the Efficiency and Effectiveness of Selecting Original Seedlings and Parents - J. K. Stringer; M. C. Cox; F. C. Atkin; X. Wei; D. M. Hogarth (Sugar Tech, 2011)

Controls on Water Levels and Salinity in a Barrier Island Mangrove, Indian River Lagoon, Florida - Christina E. Stringer; Mark C. Rains; Sarah Kruse; Dennis Whigham (Wetlands, 2010)

Trail Pheromone Disruption of Argentine Ant Trail Formation and Foraging - David Maxwell Suckling; Robert W. Peck; Lloyd D. Stringer; Kirsten Snook; Paul C. Banko (Journal of Chemical Ecology, 2010)

Reviewing the links between desertification and food insecurity: from parallel challenges to synergistic solutions - Lindsay C. Stringer (Food Security, 2009)

Historical land use and soil analysis guiding corridor landscape design - J. Renee Keydoszius; S. Knight Cox; Mary B. Haque; Elena Mikhailova; Christopher J. Post; William C. Stringer; Mark A. Schlautman (Urban Ecosystems, 2007)

Comparison of partial sequence of the cap binding protein (eIF4E) isolated from Agaricus bisporus and its pathogen Verticillium fungicola - A.L. Athey-Pollard; M. Kirby; S. Potter; C. Stringer; P.R. Mills; G.D. Foster (Mycopathologia, 2003)

Invariant recognition of feature combinations in the visual system - M. C. M. Elliffe; E. T. Rolls; S. M. Stringer (Biological Cybernetics, 2002)

Quarantine and regulatory issues pertaining to use of ca and/or fumigation - A. Carpenter; C. W. van Epenhuijsen; I. A. N. Stringer; Y. L. Ren; J. M. Desmarchelier; Judith Downey; G. Eddy; H. J. Banks; J: van S. Graver (Phytoparasitica, 2001)